Prototype Of Soil Analyzer Devices Based On Long Range (LoRa) Communication System - Febrin Aulia Batubara Batubara; Bakti Viyata Sundawa; Muhammad Rusdi (Institute of Computer Science (IOCS), 2021)
Problems of environmental damage caused by palm oil industry has become a global issue. This is often an obstacle to development of palm oil industry in Indonesia. In fact, millions of Indonesians work in palm oil sector and they are a source of state income from non-oil and gas. For this reason, efforts to support a sustainable palm oil industry need to be made. One of them is application of a smart system in palm oil industry. Soil analyzer tool is a smart system in palm oil industry. Rainfall, soil pH, temperature and humidity as well as lighting are environmental parameters that affect the growth and development of palm oil plants. Measurement results can be accessed and displayed in real-time based on LoRa technology. It is hoped that this soil analyzer will be a solution to environmental problems and related parties can determine mitigation actions in the most extreme conditions average of rainfall is 2.8 mm/day. Average of soil PH is 5.5. Average of light intensity is 10.146 lux. Average of temperature is 30.170C. Average of humidity is 70.57%.